?SUPPLEMENT ATION OF TRADITIONAL PAKISTANI FOODS WITH VEGET ABLE PROTEINS (Biological Sciences - PJSIR, 1994)
Supplementation of traditional foods with 5% (w/w basis) low fibre detoxified mustard seed meal improvednutritive value of Pakistani dishes. Fortified dishes were readily acceptable to the consumers.